2021
DOI: 10.3390/plants10071298
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Energy Recovery in Form of Biogas, from Vegetable and Fruit Wholesale Markets By-Products and Wastes, with Pretreatments

Abstract: Residues and by-products from vegetables and fruit wholesale markets are suitable for recovery in the form of energy through anaerobic digestion, allowing waste recovery and introducing them into the circular economy. This suitability is due to their composition, structural characteristics, and to the biogas generation process, which is stable and without inhibition. However, it has been observed that the proportion of methane and the level of degradation of the substrate is low. It is decided to study whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The summer FVW mixture resulted in the highest (87.96%) percentage of easily biodegradable matter, probably due to the higher content of fruits. A lower sCOD/tCOD (24.09%) for laboratory-prepared residues from vegetable and fruit wholesale markets was reported by Morales-Polo et al [16], who demonstrated the variability of substrates, whose composition is due to factors such as level of sale, consumer inclination, and season [8].…”
Section: Physical-chemical Characteristics Of the Fruit And Vegetable...mentioning
confidence: 74%
See 1 more Smart Citation
“…The summer FVW mixture resulted in the highest (87.96%) percentage of easily biodegradable matter, probably due to the higher content of fruits. A lower sCOD/tCOD (24.09%) for laboratory-prepared residues from vegetable and fruit wholesale markets was reported by Morales-Polo et al [16], who demonstrated the variability of substrates, whose composition is due to factors such as level of sale, consumer inclination, and season [8].…”
Section: Physical-chemical Characteristics Of the Fruit And Vegetable...mentioning
confidence: 74%
“…In this context, the physical-chemical FVW characteristics, highly dependent on the local waste composition and seasonal variability [4,5,16], are a relevant aspect barely investigated to better evaluate how a substrate is inclined to anaerobic degradation. Indeed, the substrate composition affects H 2 yield and production rate [17].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies recommend the application of different pretreatment techniques (physical, chemical, and biological) to enhance the biogas yield from different feedstocks. Morales‐Polo et al 226 . confirmed this by applying freezing, ultra‐freezing, and lyophilization as a pretreatment of fruit waste and byproducts, and generating 91.28 NmL per 100 g and 32.25% biogas and methane, respectively.…”
Section: Fruit Waste and Byproduct Valorization Into Biofuelsmentioning
confidence: 87%
“…As shown in Table 14, different fruit wastes are also potential candidates for biogas production. Considering the multiple functions and demands of biogas, feedstocks from different sources, including waste from fruit and vegetable production and processing, have been investigated, and have attracted interest due to their availability and high organic matter and moisture content 226 . Beyond composition, the high moisture content and high availability accounting for 33% of fruit and vegetable waste and byproducts make them a potential candidate for biogas production.…”
Section: Fruit Waste and Byproduct Valorization Into Biofuelsmentioning
confidence: 99%
“…However, the agri-food industry is a major producer of waste and by-products, both globally and in the primary sector. Material from the food supply chain can be vegetable and fruit waste [32], harvest waste and crop waste of other origin [33].…”
Section: Introductionmentioning
confidence: 99%